Global Inequality : Rethinking Sociology in the 21st Century - Wimmer, Christopher, (Social Sciences E-Books Online, Collection 2026., 2025)
The book contributes to a better understanding of the relationship between globalisation and transnationalisation and the development of social inequality. It addresses this challenge in the current transition to a multi-centred world. The contributions by international experts from different continents and different disciplines bring together current research on global inequality and social classes, covering a wide variety of thematic and spatial foci. This also includes a comparison of analyses of inequality in a global context. By bringing together analyses of inequalities in income, wealth, education, political influence, labor conditions, and socio-ecological inequalities, among others, the volume provides deeper insights into the ways in which global social inequalities are changing yet being reproduced in many ways in the 21st century. It calls for a discussion on the global dimensions of unequal power relations.